2,2-Dichloro-N-(4-chlorophenylsulfonyl)acetamide - B. Thimme Gowda; Sabine Foro; P. G. Nirmala; B. P. Sowmya; Hartmut Fuess (Acta Crystallographica Section E, 2008)
In the crystal structure of the title compound (N4CPSDCAA), C8H6Cl3NO3S, the conformations of the N—H and C=O bonds in the SO2—NH—CO—C group are trans to each other, similar to those observed in 2,2-dichloro-N-(phenylsulfonyl)acetamide (NPSDCAA), 2,2-dichloro-N-(4-methylphenylsulfonyl)acetamide (N4MPSDCAA) and N-(4-chlorophenylsulfonyl)-2,2,2-trimethylacetamide (N4CPSTMAA), with similar bond parameters. The –SNHCOC– unit in N4CPSDCAA is essentially planar and makes a dihedral angle of 79.67 (5)° with the benzene ring, comparable to 79.75 (8)° in NPSDCAA, 81.02 (5)° in N4MPSDCAA and 82.2 (1)° in N4CPSTMAA. The molecules in N4CPSDCAA are linked into layers parallel to the (001) plane by intermolecular N—H...O hydrogen bonds.